2011
DOI: 10.1007/s10509-011-0925-1
|View full text |Cite
|
Sign up to set email alerts
|

Computation of families of periodic orbits and bifurcations around a massive annulus

Abstract: This paper studies the main features of the dynamics around a planar annular disk. It is addressed an appropriated closed expression of the gravitational potential of a massive disk, which overcomes the difficulties found in previous works in this matter concerning its numerical treatment. This allows us to define the differential equations of motion that describes the motion of a massless particle orbiting the annulus. We describe the computation methods proposed for the continuation of uni-parametric familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies have continued the periodic orbit and found period-doubling bifurcations as well as pseudo period-doubling bifurcations of periodic orbit families in the gravitational field of asteroid 216 Kleopatra. This work is quite different from the continuation of the periodic orbit in the gravitational field of a simple-shaped body, such as a finite straight segment (Elipe and Lara 2003), a solid circular ring (Broucke and Elipe 2005), a homogeneous cube (Liu et al 2011), and a massive annulus (Tresaco et al 2012). The continuation of the periodic orbit in the gravitational field of a simple-shaped body can help one to understand the periodic orbit families, bifurcation of periodic orbit families, and stability of orbits around irregular minor celestial bodies.…”
Section: Casesmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have continued the periodic orbit and found period-doubling bifurcations as well as pseudo period-doubling bifurcations of periodic orbit families in the gravitational field of asteroid 216 Kleopatra. This work is quite different from the continuation of the periodic orbit in the gravitational field of a simple-shaped body, such as a finite straight segment (Elipe and Lara 2003), a solid circular ring (Broucke and Elipe 2005), a homogeneous cube (Liu et al 2011), and a massive annulus (Tresaco et al 2012). The continuation of the periodic orbit in the gravitational field of a simple-shaped body can help one to understand the periodic orbit families, bifurcation of periodic orbit families, and stability of orbits around irregular minor celestial bodies.…”
Section: Casesmentioning
confidence: 97%
“…As a periodic orbit continues(Hé non 1965;Tresaco et al 2012), the topological cases of the periodic orbit may change, and period-doubling bifurcation may occur. The period-doubling bifurcation occurs if and only if 2 or 4 Floquet multipliers collide at -1 and leave the original region.…”
mentioning
confidence: 99%
“…Distribution of six characteristic multipliers of the periodic orbit determines the topological classifications of periodic orbits [35]. The topological classifications of stable periodic orbits [17] have 7 different cases, which is listed in Table 1.…”
Section: Stability Of Periodic Orbitsmentioning
confidence: 99%
“…For studies on some general features of the dynamics around a massive annulus, like orbit stability for various configurations and the equilibrium of the system, see. e.g., [67,91,92,93,94,95] and [96].…”
Section: Introductionmentioning
confidence: 99%